Indeed, not really a brain disorder: Implications for reductionist accounts of addiction. (2019) - Field, Matt; Heather, Nick; Wiers, Reinout W.
Abstract: Borsboom et al.'s formulation provides an opportunity for a fundamental rethink about the "brain disease model" of addiction that dominates research, treatment, policy, and lay understanding of addiction. We also demonstrate how the American opioid crisis provides a contemporary example of how "brain disease" is not moderated by the environmental context but is instead crucially dependent upon it.